Consequences of Enlightenment - Cascardi, Anthony J., 1953- (Cambridge, U.K. ; New York : Cambridge University Press, 1999)
What is the relationship between contemporary intellectual culture and the European Enlightenment it claims to reject? In Consequences of Enlightenment, Anthony J. Cascardi revisits the arguments advanced in Horkheimer and Adorno's seminal work Dialectic of Enlightenment. Cascardi argues against the view that postmodern culture has rejected Enlightenment beliefs and explores instead the continuities contemporary theory shares with Kant's theory of judgment. The positive consequences of Kant's failed ambition to bring the project of Enlightenment to completion, he argues, are evident in the aesthetic basis on which subjectivity has survived in the contemporary world.
Cascardi explores the link between aesthetics and politics in thinkers as diverse as Habermas, Derrida, Arendt, Nietzsche, Hegel, and Wittgenstein in order to reverse the tendency to see works of art simply in terms of the worldly practices among which they are situated. Works of art, he argues, are themselves capable of disclosing truth. The book explores the post-Enlightenment implications of Kant's claim that feeling, and not only cognition, may provide a ground for knowledge.
1. The consequences of Enlightenment -- 2. Aesthetics as critique -- 3. The difficulty of art -- 4. Communication and transformation: aesthetics and politics in Habermas and Arendt -- 5. The role of aesthetics in the radicalization of democracy -- 6. Infinite reflection and the shape of praxis -- 7. Feeling and/as force.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Horkheimer, Max, -- 1895-1973.; Horkheimer, Max, -- 1895-1973.; Philosophische Fragmente (Horkheimer, Max); Aesthetics -- Political aspects; Aesthetics, Modern -- 20th century; Enlightenment; Aesthetics, Modern; Esthétique -- Aspect politique; Esthétique -- 20e siècle.; Siècle des Lumières.; Enlightenment (18th-century western movement); PHILOSOPHY -- History & Surveys -- Modern; PHILOSOPHY -- History & Surveys -- General; Aesthetics, Modern; Aesthetics -- Political aspects; Enlightenment; Philosophie; Rezeption; Aufklärung; Dialektik der Aufklärung (Adorno & Horkheimer); Postmodernisme; Verlichting (cultuurgeschiedenis); Esthetica; 1900-1999; Electronic books; Electronic books